2004
DOI: 10.1001/archinte.164.15.1662
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Perceptions of the Problem of Antimicrobial Resistance in Health Care Facilities

Abstract: Clinicians perceive AR to be a complex national problem but less relevant to their own institution or practice. Providing clinicians with information and steps for preventing AR, as in the Campaign, may affect their perceptions of the problem and motivate them to take actions to ensure patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 24 publications
4
75
1
3
Order By: Relevance
“…This falsely held belief is considered to be a primary barrier which prevents the development of antibiotic resistance [19].…”
Section: Resultsmentioning
confidence: 99%
“…This falsely held belief is considered to be a primary barrier which prevents the development of antibiotic resistance [19].…”
Section: Resultsmentioning
confidence: 99%
“…Information from these sources may vary widely and conflict with what is considered best practice at an institution. Although the vast majority of physicians recognize antimicrobial resistance as an important problem, most underestimate the true degree of antimicrobial resistance in their own institutions (58,160). Physicians are primarily concerned with the effects of antimicrobials in the individual patients whose care they have been charged with; in a hypothetical case scenario, the risk of contributing to antimicrobial resistance was rated lowest among seven factors influencing a physician's choice of antimicrobial agent (107).…”
Section: Education and Guideline Implementation Strategiesmentioning
confidence: 99%
“…[21][22][23][24][25] These previous studies have found that 87% to 97% of respondents viewed resistance as a national problem while fewer (55% to 93%) viewed resistance as a local problem. 17,19,[21][22][23][24] In contrast, we found that the vast majority of respondents at our institution agreed that MDR-GNB infections were a serious problem in ICUs both in the U.S. and at our medical center. Both ID and ICU healthcare professionals shared this attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, improving prescribing in the acute care setting can preferentially focus on understanding prescribers' knowledge, attitudes, and practices to identify potential barriers to optimal care. 19 We sought to address these complex issues among healthcare professionals caring for adult and pediatric patients hospitalized in ICUs and focused on treatment of infections caused by MDR-GNB, including respondents' confidence using antimicrobial susceptibility data and their perceptions of the impact of antimicrobial susceptibility testing on patient outcomes. To our knowledge, only one previous study has been conducted among a similar group of Australian providers which found that 89% of ID and ICU healthcare providers believed that results of susceptibility testing were an important influence on their antimicrobial prescribing.…”
Section: Discussionmentioning
confidence: 99%